Reduction of Post-Harvest Food Losses and Waste - Timmermans, Toine (2018)
This presentation is part of the Wageningen University & Research food loss and waste project and in association with CCAFS research program. The presentation Reduction of post harvest losses and waste was presented by Toine Timmermans in November of 2017.